Severe Lymphopenia During Neoadjuvant Chemoradiation for Esophageal Cancer: A Propensity Matched Analysis of the Relative Risk of Proton versus Photon-Based Radiation Therapy - Shiraishi, Yutaka (Radiother Oncol, 2017)
BACKGROUND AND PURPOSE: Circulating lymphocytes are exquisitely sensitive to radiation exposure, even to low scattered doses which can vary drastically between radiation modalities. We compared the relative risk of radiation-induced lymphopenia between Intensity Modulated Radiation Therapy (IMRT) or Proton Beam Therapy (PBT) in esophageal cancer (EC) patients undergoing neoadjuvant chemoradiation therapy (nCRT). MATERIAL AND METHODS: EC patients treated with IMRT and PBT were propensity matched based on key clinical variables. Treatment-associated lymphopenia was graded using CTCAE v.4.0. Using matched cohorts, univariate and multivariable multiple logistic regression was used to identify factors associated with increased risk of grade 4 lymphopenia as well as characterize their relative contributions. RESULTS: Among the 480 patients treated with nCRT, 136 IMRT patients were propensity score matched with 136 PBT patients. In the matched groups, a greater proportion of the IMRT patients (55/136, 40.4 %) developed grade 4 lymphopenia during nCRT compared with the PBT patients (24/136, 17.6 %, P < 0.0001). On multivariable analysis, PBT was significantly associated with a reduction in grade 4 lymphopenia risk (odds ratio, 0.29; 95% confidence interval, 0.16 to 0.52; P < 0.0001). CONCLUSION: PBT is associated with significant risk reduction in grade 4 lymphopenia during nCRT in esophageal cancer.